Development of Differentiated Project Based Learning Teaching Modules to Foster Critical and Creative Thinking Skills in Students - Nada, Nadila Qothrun; Astuti, Budi; Rusilowati, Ani; Hartono, Hartono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
Teaching modules are one of the teaching tool innovations in the Merdeka Curriculum. Differentiated Project Based Learning (PjBL) teaching modules are teaching tools that are tailored to the needs and characteristics of students. This study aims to develop differentiated teaching modules with the PjBL model in fostering students' critical and creative thinking skills in schools with different accreditation and analyzing the characteristics, feasibility and students' responses to teaching modules. The research method used is Research and Development (RnD) with the ADDIE model which consists of five stages, namely Analysis, Design, Development Implementation and Evaluation. The data analysis technique used is feasibility analysis with expert judgment assessment method based on V-Aiken's scale and percentage. The characteristics of the developed teaching module are using a differentiated PjBL model in learning activities and presenting questions according to critical and creative thinking indicators. The results of the feasibility test of differentiated PjBL teaching modules showed a V-Aiken's value of 0.91 for A accredited schools and 0.90 for B accredited schools with ''valid'' criteria. The results of students' responses to the LKPD which is part of the differentiated PjBL teaching module have a percentage of 88% with the criteria ''very interesting''. This shows that the differentiated PjBL teaching module is feasible to use in the physics learning process at all levels of school accreditation.